Analysis of estimation methods for resting metabolic rate in critically ill adults - Frankenfield, David C; Coleman, Abigail; Alam, Shoaib; Cooney, Robert N (JPEN. Journal of parenteral and enteral nutrition, 2009)
Prediction of metabolic rate is an important part of the nutrition assessment of critically ill patients, yet there are limited data regarding the best equation to use to make this prediction. Standardized indirect calorimetry measurements were made in 202 ventilated, adult critical care patients, and resting metabolic rate was calculated using the following equations: Penn State equation, Faisy, Brandi, Swinamer, Ireton-Jones, Mifflin, Mifflinx1.25, Harris Benedict, Harris Benedictx1.25, Harris Benedict using adjusted weight for obesity, and each of the adjusted weight versions of Harris Benedictx1.25. The subjects were subgrouped by age and obesity status (young nonobese, young obese, elderly nonobese, elderly obese). Performance of each equation was assessed using bias, precision, and accuracy rate statistics. Accuracy rates in the study population ranged from 67% for the Penn State equation to 18% for the weight-adjusted Harris Benedict equation (without multiplication). Within subgroups, the highest accuracy rate was 77% in the elderly nonobese using the Penn State equation and the lowest was 0% for the weight-adjusted Harris Benedict equation. The Penn State equation was the only equation that was unbiased and precise across all subgroups. The obese elderly group was the most difficult to predict. Therefore, a separate regression was computed for this group: Mifflin(0.71)+Tmax(85)+Ve(64)-3085. The Penn State equation provides the most accurate assessment of metabolic rate in critically ill patients if indirect calorimetry is unavailable. An alternate form of this equation for elderly obese patients is presented, but has yet to be validated.